The The Subtitling Strategies and the Semantic Equivalence of Figurative Language in Now You See Me 2 Movie - Febrianto, Nazala Wahyu; Yuliasri, Issy; Warsono, Warsono (Universitas Negeri Semarang, 2019)
There are so many popular movies in Indonesia which come from Hollywood (western countries). They uses English as their language. One of the movies we can find is Now You See Me 2 Movie. Sometimes, figurative language is used inside the movie. However, it is not easy for Indonesian people to understand English. It is why subtitling becomes very important for Indonesian. The aims of this study are: (1) to explain the subtitling strategies used in subtitling figurative language in the movie and (2) to explain the degrees of semantic equivalence of the subtitling strategies. This study is a qualitative descriptive research. To collect the data, the writer used transcription and a table of tabulated script. Transcription was used to transcribe all the dialogue into a transcript. Then, it was tabulated into a table which had been set. All the data was analyzed through transcribing, reading, categorizing, analyzing, interpreting, and drawing conclusion. The result showed that there were 94 utterances of figurative language. From 94 utterances, there were 9 subtitling strategies used; they were Expansion, Paraphrase, Transfer, Imitation, Transcription, Condensation, Decimation, Deletion, and Resignation Strategy. The most used subtitling strategy was Paraphrase Strategy that shared 39.4%. It was used in 37 excerpts. Then, the result of semantic equivalence showed that Fully Equivalent shared 42.5%, Increased Meaning shared 29.8%, and Decreased Meaning shared 7.4%. The category of Non-Equivalent showed that Different Meaning shared 16% and No Meaning shared 4.3%. The Equivalent category shared 80.8% of total 100%.